Management of Early Stage, High-Risk Endometrial Carcinoma: Preoperative and Surgical Considerations - Sareena Singh; Shandhini Raidoo; Gaetan Pettigrew; Robert DeBernardo (Obstetrics and Gynecology International)
Endometrial cancer is the most common gynecologic malignancy in the developed world. Most cases are diagnosed at an early stage and have low-grade histology, portending an overall excellent prognosis. There exists a subgroup of patients with early, high-risk disease, whose management remains controversial, as current data is clouded by inclusion of early stage tumors with different high-risk features for recurrence, unstandardized protocols for surgical staging, and an evolving staging system by which we are grouping these patients. Here, we present preoperative and intraoperative considerations that should be taken into account when planning surgical management for this population of patients.